Parental Contribution to Developing Moral Character in Adolescent Social Media Users - Metra Hauliza; Irwan Satria (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The rapid development of social media has significantly influenced adolescent behavior and moral development, raising concerns about their character formation in the digital era. Objective: This study aims to determine the contribution of parents in fostering moral character in adolescents who use social media. Method: A qualitative approach with a phenomenological method was used. The research was conducted in Pagar Dewa Village, Selebar District, Bengkulu City, in 2023. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. Result: The findings reveal that parents play a significant role in shaping their children's moral character by providing education, modeling ethical behavior, and offering guidance and advice. Conclusion: Parents have a major influence on the moral development of adolescents, particularly in teaching values and setting examples in the context of social media use. Contribution: This study provides valuable insights into parental involvement in fostering moral character in adolescents, contributing to the body of knowledge on character education in the digital age.